The Italian inter-laboratory study on the detection of Pseudomonas syringae pv. actinide - Stefania LORETI; Nicoletta PUCCI; Angela GALLELLI; Paola MINARDI; Stefano ARDIZZI; Giorgio BALESTRA; Angelo MAZZAGLIA; Maria TARATUFOLO (Phytopathologia Mediterranea, 2014)
A severe form of bacterial canker of kiwifruit, caused by Pseudomonas syringae pv. actinidiae (Psa), has been detected in all the main areas of cultivation of kiwifruit (Actinidia deliciosa and A. chinensis). Since 2010 several research groups have been assessing methods and procedures to detect and identify Psa, both from symptomatic and symptomless host material. In 2011, a study to compare Psa diagnostic methods was performed with reference to Psa strains and related pathovars, and with plant extracts or DNA obtained from healthy and naturally infected leaves, pollen or wood. The study revealed the strengths and the weaknesses of the assessed methods. The procedure included screening tests for Psa detection and for identification of Psa colonies. The methods assessed were bacterial isolation on generic and semi-selective media, PCR analysis (single, duplex and rep-PCR assay, the latter for identification only). The results highlighted the best performance of semi-selective with respect the generic media; the usefulness of the direct-PCR as screening tests for Psa detection; and the greater specificity of duplex-PCR and sensitivity of simple-PCR. The use of semi-selective medium for isolation and of two PCR-based methods - in parallel - for Psa detection are suggested. Both rep-PCR and duplex-PCR, were found to be specific, and are recommended as an identification test for this pathogen.